The Effectiveness of Mirror Therapy on Muscle Strength Rehabilitation in Non-Haemorrhagic Stroke Patients: Literature Review - Barbosa, Adirson; Septianingrum, Yurike (Chakra Brahmanda Lentera Institute, 2024)
Background: Stroke remains one of the significant problems of long-term disability. Most stroke patients have difficulty performing daily activities due to paresis of the upper limbs, resulting in impaired activities of daily living (ADL) and decreased quality of life. The purpose of this literature review is to find out the Application of Mirror Therapy to Muscle Strength Rehabilitation in non-homorrhagic stroke Patients. Methods: The method used is literature review (PRISMA) using journal databases from PubMed, Science Direct, and Google Scholar in the range 2020-2024 with the keywords